Towards an ethically justified model for access to healthcare in Zimbabwe - Moyana, Farayi (My University, 2022)
This study was conducted in order to provide a possible solution to the myriad of healthcare access problems affecting Zimbabwe. A desktop analytic review of literature, reports, legal and policy documents was carried out on the historical development of healthcare delivery in Zimbabwe spanning the pre-colonial, colonial, and post-colonial periods. Relevant literature was identified by electronic searches using Mendeley, Google chrome, and other internet search platforms. Summaries of the articles were analyzed for emerging themes and conclusions were drawn. This thesis traces the development of healthcare policies in Zimbabwe starting from the preindependence period to the post-independence period (2020). It critically analyses the egalitarian, utilitarian, and ubuntu moral theories bringing out their potential application to the design of a new model that has the potential to address challenges of access to healthcare in Zimbabwe. Selected influential healthcare models and systems such as the Beveridge, Bismarck, National Health Insurance, Single-payer systems, Multi-payer systems, and the Out-of-Pocket Spending systems are also critiqued, based on their social, legal, and ethical relevance to the aims and objectives of this thesis. The thesis presents a suggested new ethically justified healthcare model for Zimbabwe, called the Citizen Centred Healthcare Model (CCHM). It is premised on six fundamental building pillars or blocks which guarantee human rights and citizen-oriented service provision: Prioritized Healthcare Financing, Equitable Rationing of Healthcare Services, Social Solidarity and Human Rights Culture Promotion, Effective Monitoring and Evaluation, Inclusive Healthcare and Stable Political and Macroeconomic Environment.
A thesis submitted in fulfilment of the degree of Doctor of Philosophy in Bioethics and Health Law to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2022